India's socio-economic database : surveys of selected areas - Chandrasekhar, C. P.; Tilak, Jandhyala B. G. (New Delhi : Tulika, 2001)
Revision of papers presented at a seminar organized by ICSSR, at the Indian Statistical Institute, New Delhi, on 30 June-1 July, 1997.
Includes bibliographical references.
Keywords: Sociology